About International Conference MITI2018 - Ina Ciobanu; Svetlana Cojocaru; Mircea Petic (Computer Science Journal of Moldova, 2018)
The conference is a homage to the illustrious mathematician Valentin Belousov, the founder of the Theory of Quasigroups and Loops in the former USSR, doctor habilitate in physics and mathematics, professor, correspondent member at the Academy of Pedagogical Sciences of the USSR, the laureate of the State Prize of the Republic of Moldova.